Implikasi Total Bisnis untuk Rantai Pasok Tepung Tapioka dengan Menggunakan Model Green SCOR dan ANP: Studi Kasus: PD. Mekar Jaya - Cahyadi, Ujang; Tjaptajani, Dedi Sadudin; Ramdan, Dadan Muhamad (Institut Teknologi Garut, 2024)
There are many strategies that can be carried out by companies that will have implications/impacts, which in general are the main actors or network members in the tapioca flour supply chain which consists of five organizations or parties, namely suppliers, producers, distributors, retailers and consumers. Then the company must be a totality, then the nature of competition between supply chain networks then has implications for phasing in the supply chain process where the evolutionary process requires phasing so that it needs to be detailed, differentiated and planned about what, who and how for each element such as driver, focus, benefits, tools, action areas, guidelines, models, alliances and training. PD. Mekar Jaya is a company that produces tapioca flour for industrial scale which received a red rating in the program. Therefore,